Anti-diabetic activity of psychotria malayana jack leaf aqueous extract in induced type 1 diabetic adult zebrafish - Benchoula, Khaled (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Type 1 diabetes is a perpetual and profound disease impacting people at all ages. It is diagnosed with the loss of insulin production because of dynamic demolition of the β-cells in the pancreas. One bottleneck of the drug discovery on type 1 diabetes is the expensive and long testing period of the established in vivo assays. Psychotria malayana has been reported traditionally to treat diabetes. Thus, the aim of this study were to develop a type 1 diabetic adult zebrafish model through chemical induction, and to evaluate the anti-diabetic activity of Psychotria malayana Jack leaf extract on the developed type 1 diabetic adult zebrafish. Different chemical inducers, streptozotocin and alloxan, with different doses were evaluated in elevating the blood glucose level of zebrafish. Two positive controls (glibenclamide and insulin) were tested for the confirmation of the developed model. Finally, the anti-diabetic activity of a traditional medicinal plant, P. malayana aqueous extract was evaluated using the developed model. LC-MS based fingerprinting of the zebrafish and the histological examinations were applied to confirm the ability of this plant to treat type 1 diabetes. The LC-MS data set was pre-processed and then statistically calculated using a multivariate data analysis, partial least square-discriminant analysis (PLS-DA). The result of this study indicated that a single intraperitoneal injection of alloxan with the dose of 300 mg/kg was the optimal dose to elevate the fasting blood glucose level of the zebrafish. The blood glucose level (>150 mg/dL) was significantly higher (P<0.05) than that of the healthy zebrafish (70-80 mg/dL), and can be maintained for 7 days. This model was able to test the anti-diabetic activity of P. malayana leaf extract. The plant extract with the dose of 1, 2, and 3 g/kg significantly reduced the blood glucose level of the diabetic zebrafish from (123.50±10.89) to (75.67±17.82, 90.83±7.86, and 73.50±7.66, respectively) (P< 0.05). Furthermore, LC-MS based fingerprinting exhibited that all doses of the plant extract were able to shift the serum metabolite profile of the treated zebrafish toward the healthy group alongside PLS-DA component 2. While PLS-DA component 1 indicated that the plant extract with the dose of 3 g/kg was superior compared to other doses in shifting the metabolite profile toward the healthy zebrafish. Finally, the histopathological examination showed that this plant extract could not repair the enormous reduction of the Langerhans cells in the pancreas of the diabetic zebrafish. In addition, this extract did not affect the liver structure of the healthy zebrafish. Hence, the mode of action of this plant extract in lowering the blood glucose level should not be through the recovery of the pancreas, but through other mechanisms which is recommended to be examined in future research.